Comparative study of 3D-Printable polymers for beta interaction behaviours via monte carlo simulations - Hisiroglu, Kevser A.; Akcali, Ozgur; Toker, Ozan; Icelli, Orhan (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
The rapid advancement of 3D printing technologies has revolutionised production in many sectors due to the versatile properties of printable materials. Thermal, mechanical and functional performance of 3D printable components make them suitable for use in radiation-intensive environments such as betavoltaic cells and clinical phantoms. This study investigates the behaviour of 3D-printable materials, including ABS, PLA, PETG, TPU, and UV resins, under exposure to various beta radiation sources, such as H-3, Ni-63, C-14, Pm-147, Tc-99, Sr-90, and Y-90, through a comparative analysis of their beta radiation attenuation efficiency, energy absorption, and dose transmission characteristics. TPU exhibited a surface flux reduction of approximately 72.3 % for tritium (H-3) and 69.8 % for nickel-63 (Ni-63) at a thickness of 0.1 mu m, demonstrating better attenuation performance for low-energy beta radiation. A new metric, Half Absorption Thickness (HAT), was introduced to quantify the shielding capacity more precisely; the lowest HAT was found for TPU under H-3 (0.08 mm), and the highest for PETG under Tc-99 (1.12 mm). The derived logarithmic models (R-2 > 0.99) enable estimation of shielding efficiency as a function of material thickness and beta energy. Among all tested combinations, ABS exhibited the best attenuation performance against high-energy beta particles, with a maximum flux reduction of 87.1 % for Sr-90 and a corresponding HAT of 0.48 mm, establishing it as the most efficient barrier material in the studied energy range. Conversely, UV-cured resin demonstrated the highest beta transmission, particularly under H-3 and Ni-63 exposure, making it a suitable candidate for applications where controlled dose delivery is desired. These findings contribute to the literature by offering a comparative evaluation of the attenuation performance of 3D printable materials against different beta radiation sources and by providing a basis for material selection in beta applications.
Keywords: Beta radiation; 3D printable materials; MCNP; Half attenuation thickness; Nuclear Science & Technology